Commentary on the judgments of the Constitutional Court 8/2024, of january 16, and 18/2024, of january 31: “Alberto Rodríguez case” - Ruiz Bursón, Francisco Javier (Journal of the Basque Parliament, 2024)
The sentences analyzed have singular relevance in two aspects: the correct understanding of technicallegal concepts of a criminal nature, such as the principle of proportionality, analogy and extensive interpretation, as well as the analysis of the limits of the Constitutional Court in relation to the functions attributed to other powers of the State, especially the judicial and legislative.
Keywords: principle of proportionality, criminal legality, analogy, extensive interpretation, constitutionality control